Age-related knowledge deficit and attitudes towards oral implants: Survey-based examination of the correlation between patient age and implant therapy awareness - Ina Nitschke; Kristina Krüger; Julia Jockusch (BMC, 2024)
Abstract Background Implantology, as a recognized therapeutic approach, is gaining prominence. The decision-making process and success of implant therapy are closely linked to patient knowledge and expectations. This study aims to explore the association between age and knowledge regarding oral implants. Methods Participants were categorized into three age groups (ag): ag 1 (35-44 years), ag 2 (65-74 years), and ag 3 (75 years and older). A total of 400 participants per age group were randomly selected using data from the residents' registration office of Berlin, Germany. Structured telephone interviews were conducted between 2016 and 2017, employing a 67-item questionnaire covering awareness, information level, cost estimation, attitudes, and experiences with oral implants. Results Despite a low overall knowledge level across all age groups, there was no significant correlation between age and knowledge about oral implants. Awareness increased with age. Information sources varied, with friends, acquaintances, and dentists playing key roles. Participants expressed diverse opinions on implants, with durability and stability identified as crucial characteristics. Significant differences in knowledge were observed between age groups regarding awareness, information sources, and perceptions of dentists offering implants. Conclusions The study suggests a need for targeted educational programs, emphasizing age-appropriate information sources to enhance health literacy in oral implantology, particularly among older individuals. Educating physicians on oral implant basics is also crucial. Implementing these measures could empower individuals to make informed decisions about oral implant treatment, thereby contributing to improved oral health outcomes.